Socioeconomic Analysis of the Potential Benefits of Modernizing Hydrometeorological Services in the Lao People’s Democratic Republic - Global Facility for Disaster Reduction and Recovery (World Bank, Washington, DC, 2019)
The Lao People’s Democratic Republic (PDR) is exposed to significant climate and disaster risks. The country’s rapid economic development can put more people and assets at risk from natural hazards, if investments in risk reduction, planning, and preparedness are not made. The results of this analysis show that the contribution of hydrometeorological information to socioeconomic development in Lao PDR is expected to be very high, particularly due to the potential benefits for the energy and tourism sectors and their contribution to gross domestic product (GDP). The results of this study support the conclusion that hydromet information is critically important for Lao PDR and that investments in the hydromet sector are expected to be highly profitable from socioeconomic perspective.